Interlanguage and radicalization of de french female speech in North Africa and Sub-saharan Africa - (:unkn) unknown (My University, 2017)
The present study aims at analyzing the female speech in the texts of Assia Dejbar, Calixthe Beyala, Aminata Sow Fall and Nedjma. The title of the research accounts for two major concepts: interlanguage and radicalization. We base our reflection on three main bets, the first one, defines the interlanguage and questions the existence or not of objectives common to its use by women novelists. The second part, analyzes through new theoretical and critical approaches on language, novels Nowhere in my father's house, Naked woman, black woman, The strike of the battu and the almond. The third part deals with the notion of radicalization by emphasizing the language of the body, reflected in the whole of writing. The reading of the literary texts allowed to divide them into two categories. On the one hand, there are novels that lash and fight by means of a modest and reserved language, and, on the other hand, those who denounce and affirm themselves, through an extremely transgressive and violent language
Keywords: African Research